Thin capitalisation as an aggressive form of international tax planning: a comparative approach - Burgos Arredondo, Jorge; Sepúlveda Garcés, Patricia (Revista de Estudios Tributarios, 2016)
The article thereafter developed aims to provide general ideas on thin capitalisation, understanding it as a type of aggressive international tax planning. Moreover, generally speaking it is developed the way in which the doctrine and the comparative legislation have tried to resolve the pernicious effects of thin capitalisation through two kinds of rules: objective and subjective thin capitalisation rules. Afterwards, it is provided an approach of how tax adminsitrations could address the problem of thin capitalisation from the use of Double Taxation Agreements through the application of the article 9. Finally, thin capitalisation is linked to the BEPS project, not only considering Action 4, but all the actions that could interact with thin capitalisation.